NEED ASSESSMENT OF DESIGNING MATERIALS FOR PUBLIPRENEUR BASED LANGUAGE LEARNING (PBLL) - Zalzulifa Zalzulifa (Jurnal Ilmiah Publipreneur, 2020)
The research Need Assessment is necessary to make the decisions that influence a learner’s progress. It should therefore be viewed as a fundamental practice that happens naturally in the teaching and learning process. This then means that learners should be assessed continuously to monitor their progress and make daily instructional decisions. The research background was done through the learning process at the State Polytechnic of Creative Media. In finding the right way of designing English material for the publishing students the researcher executed students’ need assessment through questionnaire, interview and class observation (simulation) in learning process. The research question is overcome through eight items of respondents’ understanding, namely: 1) Perception of Lecturers toward the publishing knowledge; 2) Institutional Awareness of Lecturer; 3) Students’ role in learning activities; 4) lecturers’ role in learning process;  5) Evaluation in learning process; 6) Difficulties in designing English materials; 7) Solution in problem solving; 8) Designing English material for the publishing students. The findings of this research cover three main points. First, in order to meet the publishing students’ needs, the design of English learning materials should be formulated according to the level of competencies approaches to national qualification framework of Indonesia. Second, in order to meet the Industrial needs, the design of English learning materials must be able to promote students in performing various technical skills and publishing competencies needed for industry. Third, in order to improve students’ proficiency in understanding EOP materials, the design of English learning materials can ellaborate  Kathelen Graven’s model with its modification by putting actualizing concept after conceptualizing contents.